المؤسسات العلمية والفكرية في المدينة المنورة في عهد الرسول "صلى الله عليه وسلم" وعصر الخلفاء الراشدين رضى الله عنهم 1-40 هـ. / 622-660 م. - جانودي، محاسن محمد (جامعة دمشق, 2021)
تعد المدينة المنورة فيض الحضارة العربية الإسلامية وانطلاقها، تلك الحضارة التي أملتها ظروف الزمان والمكان، وقد استهدفت مصلحة البشرية جمعاء، فنشأت نتيجة ذلك حياة عقلية وثقافية لها طابعها الخاص، وكان ذلك مقدمة لظهور المؤسسات التعليمية في المدينة المنورة التي بدأت تتوالى تباعا أمام التقدم الحضاري. ونظرا لأهمية مؤسسات التعليم في تدعيم الحضارة العربية الإسلامية جاءت هذه الدراسة كجزء مهم وضروري في محاولة منها لتسليط الضوء على أحد أهم الموضوعات ذات الأهمية التعليمية والتربوية التي كانت بمثابة العمود الفقري والقلب النابض لفهم كثير من التوجيهات الفكرية والثقافية. وقد قسمت هذه الدراسة ذات الأهمية التعليمية إلى مقدمة وثلاثة مباحث، فبعد المقدمة، وتبيان الأهمية، والهدف من اختيار البحث، جاء المبحث الأول للحديث عن مسجد المدينة "النبوي"، ودوره في الحركة العلمية، وقد خصص لمناقشة خمسة محاور، وقد ناقش المحور الأول التعليم في المسجد النبوي في عهد الرسول صلي الله عليه وسلم 1-11ه/ 622- 632م، وأما المحور الثاني فتطرق إلى المسجد النبوي في عصر الخلفاء الراشدين رضي الله عنهم 11-40ه/632- 660م الذي جرى فيه مناقشة عدة قضايا تعليمية، هي: أ- التعليم في المسجد في عهد الخليفة أبو بكر الصديق رضي الله عنه 11- 13ه/ 632- 634م ب - التعليم في المسجد النبوي في عهد الخليفة عمر بن الخطاب رضي الله عنه 13- 23ه/ 634-643م ، ج- التعليم في المسجد النبوي في عهد الخليفة عثمان بن عفان رضي الله عنه 23- 35ه/ 643-655م، د-التعليم في المسجد النبوي في عهد الخليفة علي بن أبي طالب رضي الله عنه 35- 40ه/655- 660م. ثم انصب اهتمام البحث على المحور الثالث، وقد تضمن رواد العلم والتعليم في عهد الرسول صلي الله عليه وسلم وعصر الخلفاء الراشدين رضي الله عنهم، في حين ركز المحور الرابع على المواد التعليمية في المسجد في عهد الرسول صلي الله عليه وسلم وعصر الخلفاء الراشدين رضي الله عنهم، وهي أولا: المواد النقلية، وتشمل العلوم الشرعية، وعلوم اللغة، والعلوم الاجتماعية. ثانيا: المواد العقلية، وتشمل علم الجغرافيا، وعلم الفلك "علم النجوم"، وعلم الحساب، وعلم الطب، وعلم التمريض. ثالثا: مواد تعليمية مهمة. وقد خصص المحور الخامس للحديث عن طرق التعليم في المسجد النبوي في عهد الرسول صلي الله عليه وسلم وعصر الخلفاء الراشدين رضي الله عنهم. وأما المبحث الثاني فقد خصص للحديث عن الكتاب، وقد قسم إلى أربعة محاور، المحور الأول الكتاب في المدينة وأما المحور الثاني فتناول عطلة الكتاتيب، في حين شمل المحور الثالث أوقات التعليم في الكتاب، وقد خصص المحور الربع للحديث عن منهج كتاتيب المدينة في التعليم. في حين تناول المبحث الثالث التعريف بأقدم بيوت العلم "دار القراء" التي احتلت مكانا زاهرا في الحضارة العربية الإسلامية. وختم البحث بدراسة موجزة أجملت فيها أبرز وأهم النتائج التي توصلت إليها دراسة المؤسسات العلمية والفكرية في المدينة المنورة في عهد الرسول صلي الله عليه وسلم وعصر الخلفاء الراشدين رضي الله عنهم 1-40ه/ 622-660 م. The city of Medina is the spring of Arab Islamic civilization and its launching, acivilization that was dictated by the circumstances of time and place. It was aimed at the interest of all mankind. As a result, it created an intellectual and cultural life of its own character. Given the importance of educational institutions in strengthening the Arab-Islamic civilization, this study was an important and necessary part of an attempt to highlight one of the most important topics of educational and educational importance, which served as the backbone and heart of the spring to understand many of the intellectual and cultural directives. The first topic was to talk about the city's "prophet" mosque and its role in the scientific movement. It was devoted to discussing five axes. The first topic discussed education in the mosque The Prophet (PBUH) in the era of the Prophet (PBUH) is 1-11 AH / 622-632AD. The second axis is the Prophet's Mosque in the era of the Caliphs, 11-40 AH / 632- 660 AD, in which several educational issues were discussed: B- Education in the Prophet's Mosque under the Caliph Umar ibn al-Khattab 13-23 AH / 634-643 AD, c. Mosque of the Prophet in the era of Caliph Uthman bin Affan 23-35AH / 643-655AD, d. Education in the Prophet's Mosque during the reign of Caliph Ali bin Abi Talib, 35-40AH / 655-660AD. Then the focus of the research on the third axis, and included the pioneers of science and education under the Apostle and the era of the Caliphs, the Caliphs, while the fourth axis focused on educational materials in the mosque during the era of the Prophet and the era of the Caliphs, which are first: transport materials, including science Legitimacy, language sciences, and social sciences. Second: mental materials, including geography, astronomy, "astrology", arithmetic, medical science, and nursing. Third: important educational materials. The fifth axis was devoted to modern ways of education in the Prophet's Mosque during the reign of the Prophet and the rule of the Caliphs. The second topic was devoted to the book, divided into four axes, the first axis is the book in the city and the second axis dealt with the holiday of the writing, while the third axis included the teaching times in the book. The fourth axis was devoted to talk about the curriculum of the city's writings in education. The third topic dealt with the definition of the oldest houses of science, "House readers," which occupied a shining place of the Arab Islamic civilization. The study concluded with a brief study in which the most prominent and important findings of the study of scientific and intellectual institutions in Medina during the reign of the Prophet and the successors of the caliph:1-402AH / 622-660AD.
Keywords: الثقافة الإسلامية -- المسجد النبوي -- عصر الخلفاء الراشدين -- تاريخ العلوم -- المواد العقلية